ANALISIS MAJAS AQLIY DALAM SURAH AL-BAQARAH AYAT 2: (STUDI ANALISIS ILMU BALAGHAH) - Dinda Nur Azizah; Nina Sari Siregar; Nurlia Sari (CV. Denasya Smart Publisher, 2024)
The purpose of this article is to analyze Majaz 'Aqli, which is found in Surah Al-Baqarah. Although there are many majaz in the Qur'an, this article only discusses one verse, namely Surah Al-Baqarah verse 2. The type of research in this article is qualitative, so this research is part of a Literature Review. This research was conducted by collecting and taking data related to the topic. Data search was carried out using primary data sources in the form of the Qur'an and secondary data sources in the form of books, journals, theses and dissertations related to the title, namely